Doping Induced Gap Anisotropy in Iron-Based Superconductors: a Point-Contact Andreev Reflection Study of BaFe2−xNixAs2 Single Crystals*Supported by the National Basic Research Program of China under Grant Nos 2011CBA00100 and 2012CB821404, and the Project of International Team on Superconductivity and Novel Electronic Materials of Chinese Academy of Sciences. (July 2015) - Zhu, Jun; Wang, Zhao-Sheng; Wang, Zhen-Yu; Hou, Xing-Yuan; Luo, Hui-Qian; Lu, Xing-Ye; Li, Chun-Hong; Shan, Lei; Wen, Hai-Hu; Ren, Cong
<x content-type="archive" xml:space="preserve">Abstract</x> We report a systematic investigation on c-axis point-contact Andreev reflection (PCAR) in BaFe2−xNixAs2 superconducting single crystals from underdoped to overdoped regions (0.075≤ x ≤0.15). At low temperatures, an in-gap sharp peak at low-bias voltage is observed in PCAR for overdoped samples, in contrast to the case of underdoped junctions, in which an in-gap plateau is observed. The variety of the conductance spectra with doping can be well described by using a generalized Blonder–Tinkham–Klapwijk formalism with an angle-dependent gap. This gap shows a clear crossover from a nodeless in the underdoped side to a nodal feature in the overdoped region. This result provides evidence of the doping-induced evolution of the superconducting order parameter when the inter-pocket and intra-pocket scattering are tuned through doping, as expected in the s± scenario.